The impact of obesity on rates of post-operative CSF leak following endoscopic skull base surgery: results from a prospective international multi-centre cohort study - , CRANIAL Consortium (Frontiers in Endocrinology, 2024)
Post-operative CSF leak is the major source of morbidity following transsphenoidal approaches (TSA) and expanded endonasal approaches (EEA) to lesions of the sella turcica and the ventral skull base. There are conflicting reports in the literature as to whether obesity (BMI ≥30) is a risk factor for this complication. We aimed to evaluate data collected as part of prospective multi-centre cohort study to address this question.The CRANIAL (CSF Rhinorrhoea After Endonasal Intervention to the Skull Base) study database was reviewed and patients were divided into obese and non-obese cohorts. Data on patient demographics, underlying pathology, intra-operative findings and skull base repair techniques were analysed.TSA were performed on 726 patients, of whom 210 were obese and 516 were nonobese. The rate of post-operative CSF leak in the obese cohort was 11/210 (5%), compared to 17/516 (3%) in the non-obese cohort, which was not statistically significant (c 2 = 1.520, p=0.217). EEA were performed on 140 patients, of whom 28 were obese and 112 were non-obese. The rate of post-operative CSF leak in the obese cohort was 2/28 (7%), which was identical to the rate observed in the non-obese cohort 8/112 (7%) Fisher's Exact Test, p=1.000). These results persisted following adjustment for inter-institutional variation and baseline risk of post-operative CSF leak.CSF leak rates following TSA and EEA, in association with modern skull base repair techniques, were found to be low in both obese and non-obese patients. However, due to the low rate of post-operative CSF leak, we were unable to fully exclude a small contributory effect of obesity to the risk of this complication.